2013
DOI: 10.1179/1743281213y.0000000118
|View full text |Cite
|
Sign up to set email alerts
|

New vanadium-microalloyed bainitic 700 MPa strip steel product

Abstract: Hot rolled strips having a minimum yield stress of 700 MPa have been produced in full scale processing. Alloy additions (1?5%Mn, 1%Cr and 0?3%Mo) together with rapid cooling on the runout table produce fully bainitic microstructures which confer strength and toughness. Microalloying with 0?08%V has been shown to be essential for achieving stable strength levels that are independent of the coiling temperature since the necessary low coiling temperatures are difficult to reproduce accurately under steelworks con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In 0.042C-0.3Mo-1.0Cr-0.08V steel coiled in the temperature range of 180-530 • C, Hutchinson et al [38] observed bainitic microstructures with average ferrite grain size of 3 µm. Increased to 640-770 MPa proof stress was suggested to originate mainly from high dislocation density in bainite and, in particular, dislocation pinning by V(C,N) precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…In 0.042C-0.3Mo-1.0Cr-0.08V steel coiled in the temperature range of 180-530 • C, Hutchinson et al [38] observed bainitic microstructures with average ferrite grain size of 3 µm. Increased to 640-770 MPa proof stress was suggested to originate mainly from high dislocation density in bainite and, in particular, dislocation pinning by V(C,N) precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum: Mo increases the strength by increasing the hardenability of steel. The addition of Mo can inhibit the formation of eutectoid ferrite and pearlite during the hardening process [ 63 , 64 ], forming a small amount of overaged martensite islands and promoting the formation of hardened phases, such as bainite and martensite [ 64 , 65 ], to increase the steel yield strength. Mo is a strong carbide-forming element that is mainly present in solid solutions and carbides in alloy steel.…”
Section: Resultsmentioning
confidence: 99%
“…Photographs of typical bend tested samples are illustrated in Fig. 2a and the average values of inner-bend-angle and minimum bend-radius to thickness ratio (Rmin/t) are listed in to Hutchinson et al [30] and Datsko et al [31] the smaller the Rmin/t ratio the better the bending performance of a material. Hutchinson et al suggested Rmin/t ratio to be maintained below 2.5…”
Section: Evaluation Of Bending Performancementioning
confidence: 99%
“…for ensuring satisfactory bending performance [30] . Although the best bending ratio obtained in the present study for Ti-460 sample is 3.7, this value may not be directly comparable with the earlier studies due to the difference in specimen size.…”
Section: Evaluation Of Bending Performancementioning
confidence: 99%